Groundwater Chemistry Characterization in the South and Southeast Merapi Volcano, Indonesia - Heru Hendrayana; Agung Harijoko; Indra Agus Riyanto; Azmin Nuha; Ruslisan Ruslisan (Faculty of Geography, Universitas Gadjah Mada, 2023)
Merapi Volcano, which differs from volcanoes in other climates due to its location on the Indonesian Maritime Continent influenced by ENSO, ICTZ, and Moonsons, plays an essential role as a source of groundwater for the surrounding population. Some problems associated with groundwater in Mount Merapi are high utilization compared to other volcanoes worldwide, changes in land use, pollution, and its lowering table. Therefore, this study aims to compare the hydrogeological characteristics and aquifer systems of the southern and southeastern parts of Merapi Volcano. The hydrogeological characteristics were obtained from geological mapping, surface and subsurface, as well as rock XRF tests. Meanwhile, the hydrogeochemical characterization was determined through chemical data using the Trilinear Piper, Kurlov, Fingerprint, Composition, and Harker Diagram methods. The results of the Trilinear Piper, Kurlov, Fingerprint, and Composition Diagram methods show that Mount Merapi has 3, 7, 4, and 2 types of patterns different from other volcanoes in the world. On the other hand, the Harker diagram has the same pattern of Mg-Ca and Mg-Na as several other volcanoes. In conclusion, the hydrostratigraphy in the southern part of the volcano, consists of aquifuge, aquiclude, and aquifer, while in the southeast, there are aquitards of volcanic sandstone and tuff.